Traces and Phantom Gestures: Loss Embodied in Como si existiese el perdón, by Mariana Travacio (Letras, 2025)
This article examines how Como si existiese el perdón, by Mariana Travacio, embodies different forms of loss through two mechanisms: the trace and the phantom gesture. Loss is inscribed on the body through the plasticity of flesh, producing marks that conjure absence without explicitly naming it. The analysis focuses on the images surrounding bodies that carry these marks, drawing on concepts of body, perception, conjuration, trace, and phantom gesture developed by Jacques Derrida, Maurice Merleau-Ponty, Georges Didi-Huberman, and Meri Torras. The study argues, first, that the novel presents three forms of loss: relational, material, and somatic. Second, that scars and traces not only imply the rupture of corporeal wholeness but also signal the void left by such losses. Third, that a particular bodily expression —the phantom gesture— emerges as a way of outlining, through the body, the contour of what is absent, thereby conjuring loss. This analysis is relevant both because there exists a notable gap in the critical literature on Travacio’s fiction and because it highlights how literature can be read through the textuality and plasticity of bodies, as well as the affective dimensions of their representation.
Keywords: Embodiment of Loss; Trace; Phantom Gestures; Textuality of the Body; Affectivity